Comprehensive Analysis of Digital Health Technology: Assessing Mobile Health Applications for Managing Chronic Diseases and Promoting Patient Engagement - ALAMRI, RAZAN HAMED; ALAMRI, MANAL HAMED; ALAMRI, SHOROUQ HAMED; MOHAMMEDKHALIL, RANIAH HASSAN; ALOTAIBI, SARAH SAAD; ALBALAWI, AMAL OBEAD; ALOTAIBY, RASMIAH SAAD; ALQARNI, WALEED HASSAN (Journal of Ecohumanism, 2024)
The era of advanced digital prevalence has revolutionized almost all aspects of chronic illness and the approach to patient empowerment. Soon, mHealth solutions became essential for caring, monitoring, and implementing patient engagement. This paper includes a detailed consideration of existing literature and outcomes associated with using mHealth applications for chronic disease management and patient engagement. The results of recent literature, surveys, and users’ real data show a positive impact on disease management, patient adherence, and quality of life. However, other concerns, such as accessibility, data privacy, and user retention, remain, and adequate solutions are being called for. Recommendations are presented to enhance the use and effectiveness of mobile health strategies in clinical practice.